East Asian winter monsoon variation during the last 3000 years as recorded in a subtropical mountain lake, northeastern Taiwan. (September 2021) - Lin, Tsai-Wen; Kaboth-Bahr, Stefanie; Yamoah, Kweku Afrifa; Bahr, André; Burr, George; Chang, Yuan-Pin; Dietze, Elisabeth; Li, Hong-Chun; Su, Chih-Chieh; Yam, Rita SW; Löwemark, Ludvig
The East Asian Winter Monsoon (EAWM) is a fundamental part of the global monsoon system that affects nearly one-quarter of the world's population. Robust paleoclimate reconstructions in East Asia are complicated by multiple sources of precipitation. These sources, such as the EAWM and typhoons, need to be disentangled in order to understand the dominant source of precipitation influencing the past and current climate. Taiwan, situated within the subtropical East Asian monsoon system, provides a unique opportunity to study monsoon and typhoon variability through time. Here we combine sediment trap data with down-core records from Cueifong Lake in northeastern Taiwan to reconstruct monsoonal rainfall fluctuations over the past 3000 years. The monthly collected grain-size data indicate that a decrease in sediment grain size reflects the strength of the EAWM. End member modelling analysis (EMMA) on sediment core and trap data reveals two dominant grain-size end-members (EMs), with the coarse EM 2 representing a robust indicator of EAWM strength. The downcore variations of EM 2 show a gradual decrease over the past 3000 years indicating a gradual strengthening of the EAWM, in agreement with other published EAWM records. This enhanced late-Holocene EAWM can be linked to the expansion of sea-ice cover in the western Arctic Ocean caused by decreased summer insolation.